2019
DOI: 10.3390/app9091805
|View full text |Cite
|
Sign up to set email alerts
|

Damage Detection in Beam Bridges Using Quasi-static Displacement Influence Lines

Abstract: Quasi-static strain influence lines (ILs) based on the Brillouin optical time domain analysis (BOTDA) technique have been proposed to effectively locate damage in beam bridges. Using measurement points with a high spatial resolution, the BOTDA technique supplies enough strain ILs to help detect damage in bridges. Unlike quasi-static strain ILs based on the BOTDA technique, quasi-static displacement ILs are relatively easy to implement in actual bridges; furthermore, only a few quasi-static displacement ILs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Static influence line deflection [15][16][17] Dynamic properties are not needed. The influencing factors are loading, stiffness, and mass of bridges.…”
Section: Methods Descriptionsmentioning
confidence: 99%
“…Static influence line deflection [15][16][17] Dynamic properties are not needed. The influencing factors are loading, stiffness, and mass of bridges.…”
Section: Methods Descriptionsmentioning
confidence: 99%
“…These approaches can be broadly classified based on whether the load-response behaviour being analysed can be described using either statics, which depends only on structural stiffness, or dynamics, where the effects of inertia and damping must also be considered. Static responses obtained from strain [5], [6] can identify damage close to the sensor, whereas static response captured via displacement [7]- [9] theoretically will be affected by damage anywhere in the deck, albeit displacement is typically harder to measure on site. Bridge rotation response is also affected by damage both near and far from the sensor but it is easier to measure than displacement.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the road roughness of the bridge deck is an inherent physical phenomenon present in almost all bridges, due to construction quality and maintenance capacity. Several scholars have observed that road roughness amplifies the dynamic response due to the moving action of the mass, potentially compromising the safety and serviceability of the structure [23,24]. Existing studies exhibit certain deficiencies, primarily in the assumption that vehicles on the bridge are typically regarded as one or several separate moving load models.…”
Section: Introductionmentioning
confidence: 99%